Phylogenetic revision of Dennstaedtioideae (Dennstaedtiaceae: Polypodiales) with description of Mucura, gen. nov. - Triana Moreno, Luz A. (2023)
We undertook a molecular phylogenetic revision of hayscented ferns (Dennstaedtiaceae: Dennstaedtioideae) using four plastid markers. Our sampling represents ca. 40% of the extant diversity and includes the type species for each of the relevant segregate genera. We coded 18 discrete morphological characters which we used to find diagnosable clades. We show that Dennstaedtia is polyphyletic, with the majority of species forming three morphologically distinct clades, but its type (D. flaccida) is nested within Microlepia. As such, we support the conservation of Dennstaedtia with a new type, D. dissecta. Following our results, we develop a classification of four genera: Dennstaedtia, Microlepia, Mucura (gen. nov.) and Sitobolium. Beyond the inclusion of D. flaccida, we propose to maintain Microlepia with its current circumscription. Except for a single adventive species in the Neotropics, Microlepia is a Paleotropical genus of about 60 species diagnosed by their distinctive perispore ornamentation of rodlets, and by petioles that lack epipetiolar buds. Mucura is a Neotropical genus of two species that differ from all other Dennstaedtiaceae by the combination of dichotomously branching rhizomes, petioles that lack epipetiolar buds, marginal sori with both abaxial and adaxial indusia, and trilete spores with a unique perispore ornamentation. As defined here, Dennstaedtia is a pantropical genus of about 55 species recognized by having unbranched rhizomes, petioles bearing epipetiolar buds, and by often bearing proliferous buds upon the leaves. Sitobolium is a small clade of ca. five species distinguished by their relatively small leaves that have elongate catenate hairs. These hairs often bear a capitate non-glandular terminal cell. In support of our classification, we provide a key to the eleven genera of Dennstaedtiaceae, and for the four genera of Dennstaedtioideae we provide morphological and geographic synopses, a list of constituent species, and necessary new combinations.